2014
DOI: 10.1503/cjs.020812
|View full text |Cite
|
Sign up to set email alerts
|

A simple strategy to reduce stereotype threat for orthopedic residents

Abstract: Background: Stereotype threat, defined as the predicament felt by people in either positive or negative learning experiences where they could conform to negative stereotypes associated with their own group membership, can interfere with learning. The purpose of this study was to determine if a simple orientation session could reduce stereotype threat for orthopedic residents. Methods:The intervention group received an orientation on 2 occasions focusing on their possible responses to perceived poor performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Other published studies aimed at reducing stereotype threat among women and minorities in medicine have had mixed results, and it is plausible that, because of the so-called ''file-drawer effect,'' other unsuccessful interventions have gone unpublished. 13 For example, one intervention aimed at reducing stereotype threat for orthopedic residents was not successful, 14 although the investigators did not use the values affirmation protocol successfully utilized by Cohen and colleagues 15 in prior studies and did not measure actual performance. Another study that conducted a values affirmation with ethnic minority medical students, in a manner consistent with Cohen et al's methods, 15 found that values affirmation did lead to improved scores on 1 measure among minority group members who had completed an affirmation exercise, but this was due to decreased scores in the white intervention group; furthermore, on another measure, both white and minority students in the affirmed group outperformed controls.…”
Section: Diana Burgess Phdmentioning
confidence: 99%
“…Other published studies aimed at reducing stereotype threat among women and minorities in medicine have had mixed results, and it is plausible that, because of the so-called ''file-drawer effect,'' other unsuccessful interventions have gone unpublished. 13 For example, one intervention aimed at reducing stereotype threat for orthopedic residents was not successful, 14 although the investigators did not use the values affirmation protocol successfully utilized by Cohen and colleagues 15 in prior studies and did not measure actual performance. Another study that conducted a values affirmation with ethnic minority medical students, in a manner consistent with Cohen et al's methods, 15 found that values affirmation did lead to improved scores on 1 measure among minority group members who had completed an affirmation exercise, but this was due to decreased scores in the white intervention group; furthermore, on another measure, both white and minority students in the affirmed group outperformed controls.…”
Section: Diana Burgess Phdmentioning
confidence: 99%
“…Stereotype threat is a psychological phenomenon in which a perceived fear of fulfilling negative stereotypes about one's identity group leads to impaired performance 26 . Several studies have demonstrated that stereotype threat in medicine not only contributes to academic and occupational underperformance among medical students, but also among surgical trainees 27,28 . Vulnerability to stereotype threat is particularly pronounced among Black trainees.…”
mentioning
confidence: 99%
“…Additionally, implicit bias training for mentors and education regarding microaggression and stereotype threat provide mentors with tangible tools to provide emotional support when needed and aid in the career development of their mentees 41 . Previous studies have demonstrated that simple interventions such as emphasizing similarities among trainees, reinforcing self-worth through reflecting on positive group membership, and emphasizing positive feedback during teaching can aid in reducing the burden of stereotype threat 28,42 . Furthermore, promoting autonomy, building competence, and creating strong social relatedness are positively associated with resident well-being 43 .…”
mentioning
confidence: 99%